RESEARCHING PHOTOGRAPHIC PARTICIPATORY INQUIRY IN AN E-LEARNING ENVIRONMENT - Grushka, Kathryn Meyer; Bellette, Aaron; Holbrook, Allyson (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2015)
This article focuses on the use of Photographic Participatory Inquiry (PPI) in researching the teaching and learning of photography in the e-learning environment. It is an arts-informed method drawing on digital tools to capture collective information as digital artefacts, which can then be accessed and harnessed to build critical and reflective photographic practices. The multimedia tools employed (for example GoPro video and screen capture) are critically discussed for their potential to contribute understanding of photographic artistic practice and the learning of a digital generation. The article may also provide critical insights and inform more nuanced methods for research and scholarship when wishing to investigate the personalized, participatory, and productive pedagogies of a networked learning society. MIEUX COMPRENDRE L’ENQUÊTE PHOTOGRAPHIQUE PARTICIPATIVE DANS UN ENVIRONNEMENT D’APPRENTISSAGE EN LIGNE Cet article porte sur l’utilisation, en contexte d’apprentissage en ligne, de la photographie participative comme méthode de recherche dans le domaine de l’enseignement et de l’apprentissage de la photographie. Cette méthode, fondée sur les arts, s’appuie sur l’utilisation d’outils numériques pour recueillir de l’information sous forme d’artéfacts numériques, artéfacts pouvant ensuite être consultés et exploités pour élaborer des pratiques photographiques critiques et réflectives. Les outils multimédia utilisés (par exemple, des vidéos GoPro et des captures d’écran) et leur potentiel à contribuer à une meilleure compréhension des pratiques de photographie artistique et d’apprentissage de la génération numérique sont examinés sous un angle critique. Cet article peut également fournir des perspectives critiques et engendrer des méthodes de recherche plus nuancées pour ceux désirant enquêter les pédagogies personnalisées, participatives et productives d’une société d’apprentissage en réseau.